2015
DOI: 10.14348/molcells.2015.0005
|View full text |Cite
|
Sign up to set email alerts
|

Increased Methylation of Interleukin 6 Gene Is Associated with Obesity in Korean Women

Abstract: Obesity is the fifth leading risk for death globally, and a significant challenge to global health. It is a common, complex, non-malignant disease and develops due to interactions between the genes and the environment. DNA methylation can act as a downstream effector of environmental signals; analysis of this process therefore holds substantial promise for identifying mechanisms through which genetic and environmental factors jointly contribute to disease risk. To assess the effects of excessive weight and obe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
28
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 31 publications
1
28
2
Order By: Relevance
“…Furthermore, recent studies have demonstrated a relationship between DNA methylation and metabolic diseases, such as obesity [21]. Therefore, the methylation levels of the promoter region in the following genes IL6 , LINE1 , SERPINE1, and TNF , previously linked with this type of pathological conditions [21,31,32,33,37,38,39], were evaluated in obese subjects with SAHS, in order to examine the molecular links between resting oxygen consumption and chronic diseases. Methylation levels of IL6 and SERPINE1 were positively associated with FFM.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, recent studies have demonstrated a relationship between DNA methylation and metabolic diseases, such as obesity [21]. Therefore, the methylation levels of the promoter region in the following genes IL6 , LINE1 , SERPINE1, and TNF , previously linked with this type of pathological conditions [21,31,32,33,37,38,39], were evaluated in obese subjects with SAHS, in order to examine the molecular links between resting oxygen consumption and chronic diseases. Methylation levels of IL6 and SERPINE1 were positively associated with FFM.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, obesity has been associated with increased DNA methylation levels of IL6 gene in PBC from women [39]. Moreover, a genome-wide association study performed in European obese subjects established a positive association between BMI and hypoxia-inducible 3A locus methylation in PBC and adipose tissue, suggesting a possible role of oxygen in the response to weight gain [23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increases in markers of oxidative stress and circulating levels of inflammatory cytokines, such as IL-6 and TNFa, have been shown to alter the expression of DNA methyltransferases (DNMTs) [28][29][30][31][32] and influence DNA methylation patterns [11,33]. DNA methylation of inflammatory cytokines have been associated with various inflammatory diseases including IL6 with Rheumatoid Arthritis [34] and obesity [35]; TNF DNA methylation with type 2 diabetes [36] and Alzheimer's disease [37]. Despite increased circulating levels of inflammatory cytokines post-exercise [14,23], the impact of exercise on the DNA methylation of genes encoding inflammatory cytokines such as IL6 and TNF remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Authors believe that aberrant DNA methylation of IL6 gene promoter may play an important role in the etiology and pathogenesis of obesity and IL6 methylation could be used as molecular biomarker for obesity risk assessment because DNA methylation can act as a downstream effector of environmental signals [24]. Among the various nuclear receptors, peroxisome proliferator-activated receptor γ promotes the transcription of adiponectin and antioxidative enzymes, whereas mineralocorticoid receptor mediates the effects of aldosterone and glucocorticoid to induce oxidative stress in adipocytes.…”
mentioning
confidence: 99%